Bank liquidity provision across the firm size distribution - Chodorow-Reich, Gabriel; Darmouni, Olivier; Luck, Stephan; Plosser, Matthew (Journal of financial economics, 2022)
We use supervisory loan-level data to document that small firms (SMEs) obtain shorter maturity credit lines than large firms, post more collateral, have higher utilization rates, and pay higher spreads. We rationalize these facts as the equilibrium outcome of a trade-off between lender commitment and discretion. Using the COVID recession, we test the prediction that SMEs are subject to greater lender discretion. Consistent with this hypothesis, SMEs did not draw down whereas large firms did, even in response to similar demand shocks. PPP recipients reduced non-PPP loan balances, indicating the program bolstered their liquidity and alleviated the shortfall.